Righteousness of God : ability to live Christian holiness - Matijević, Dalia (Array, 2018)
The purpose of this article is to provide insight to what extent our conceptualization of the dikaiosyne theou shapes our way of understanding ourselves as Christians being the Body of Christ and living holy lives. Strongly influenced by the epistle to the Romans, we perceive holiness as being in right relation to God and righteousness being a practical consequence of this relationship. Holiness as the inner nature of God brings fruits of His righteousness, which is God’s saving activity. However, in the light of Christ and his sacrificial death and resurrection, relational, and eschatological perspectives of the dikaiosyne theou concept become crucial. This concept stands at the heart of Paul’s gospel and anticipates several layers of meaning, primarily God’s redeeming and saving activity, but also covenantal faithfulness and restorative justice brought by God and made available for all. Wider perspective is provided through the faithfulness of Jesus and his obedience to the Father in fulfilling salvific purposes. For us, it means a transformational and relational way of living in an eschatological perspective. Christian ethics are deeply grounded in the concept of dikaiosyne theou, and Christian conduct represents its practical and necessary expression. People living in genuine Christian community are marked by the righteousness of God expressed as agape and progressively transformed by the presence and involvement of his Holy Spirit. Such people involve themselves in a continuous process of discovering new opportunities to affirm God’s righteousness. Thus, the Christian community of faith needs to be inclusive in its nature.